Review on Mobile Apps for Digitized Diagnosis with TMAS-A Telemedical Aided System - Haritha, , Dr. A. (International Journal of Psychosocial Rehabilitation, 2020)
The tremendous changes in the technology are making the medical field to evolve on the daily basis. To be made available for the remote consumers there are lot of opportunities created due to the advent of eHealth services and equipment. One of the fast emerging section of the health care which is gaining enormous attention is Telemedicine. As specialists routinely look for better approaches to treat individuals, technology has carried various extraordinary advances to the medicinal field. There are different mobile apps available to make telemedicine possible. This paper mainly focuses on the review of the apps in different domains of telemedicine. Finally, the paper discusses a proposed architecture which is a amalgamation of different areas like IoT, Data Analytics, Cloud Storage, Artificial Intelligence to give the best of their features and finally the emergence of TMAS-Telemedicine Aided System.